Social Support In The Implementation Of The Climate Village Program (ProKlim) Through The "Kita Maju Bersama" Waste Bank In Tanjungpinang City - Toni Sevriyansah; Ari Ridho Susanto (International Journal of Taklimat Science Review, 2026)
This study aims to describe the dynamics of social support in the implementation of the Climate Village Program (ProKlim) throught the "Kita Maju Bersama" Waste Bank Of Bukit Cermin, Tanjungpinang City. Unlike previous studies that tend to position ProKlim tecnically and partrialy, this research exaimines the interconnectedness between environmental conservasion and integrated social prosesses. The research employs a qualitative method with a post-positivism paradigm. Data ware collected  throught observasion in depth interviews, and documentasion, then analyzed using Emile Durkheim's Theory of Social Solidarity. The reasults show that the success of this program, whish won the 2024 National ProKlim Lestari Trophy is driven by a macro triapartite colaboration: the lokal governmence as an administrative facilitator, the private sector (Bnak Mandiri)  as a material insfrastructure supporter, and enviromental acency (DLH)  as a cognitive aducation agent. At the micro-level the community's social ressilience is formend throught a unique intersection of mechanical solidarity (cumunal work traditional for food mitigation) and organic soliarity (fundation devision of into domestic waste sorters. upcyling artisans, and organic waste prosessors. In Comclusion environmental sustanability in this area a manifestasion of healthy social relationships, whare exological values have been independently internalized into collective consciouness and cultural capital without relying on external coercive regulations.